Implementation of patient safety culture in outcome level in X general hospital in Yogyakarta - Widi Hastuti, Siti Kurnia; Puspaningtyas, Daru Respati; Syam, Nur Syarianingsih (International Journal Of Community Medicine And Public Health, 2019)
Background: Creating a culture of patient safety is something that must be considered. This is because culture contains two important components, namely values and beliefs that can change organizations. Most safety incidents of Yogyakarta District Hospital in 2018 were 21 near miss incidents, incidents in total, then 17 incident, not injured and 5 events in unexpected events, while in potential injured there were no incidents during 2018. In 2018 there were still several months of data that had not yet met patient safety incident targets. From a preliminary study the researcher obtained, data on patient safety incident reporting has not been optimally performed by nurses. The purpose of this study was to determine the implementation of patient safety culture at the outcome level. Methods: This research is mixed methods research with an explanatory sequential design. Primary data obtained from in-depth interviews, a description of the implementation of patient safety culture at the Outcome level data obtained from questionnaires given to 72 nurses. Results: The culture of patient safety Yogyakarta District Hospital has been implemented well. At the level of patient safety culture outcomes related to the frequency of reporting patient safety events have been carried out but related to incidents that have no potential for injury when reporting is not appropriate, the perception of patient safety at the patient safety level, the number of reporting of events at the Yogyakarta District Hospital has been carried out properly. Conclusions: The safety culture of patients at Yogyakarta District Hospital at the outcome level has been implemented well.